Flat optics in high numerical aperture broadband imaging systems - Werdehausen, Daniel; Burger, Sven; Staude, Isabelle; Pertsch, Thomas; Decker, Manuel (Journal of Optics, 2020)
Diffractive optical elements (DOEs) remain highly underutilized in broadband optical systems even though different technologies for DOEs including échelette-type gratings (EGs), multilevel DOEs, and metagratings have been introduced. Specifically, nanocomposite-enabled EGs can achieve efficiencies of close to throughout the visible spectrum, but only for relatively small diffraction angles. Therefore, the question remains if they are suitable for high-numerical-aperture (NA) systems. Here we show that this is indeed the case. To this end, we first demonstrate that macroscopic nanocomposite-enabled diffractive lenses (DLs) can achieve perfect broadband focusing up to a NA of 0.03. We then derive analytic relationships and investigate prototypical optical designs to show that this threshold fully covers the requirements of high-end imaging systems with This holistic all-system analysis demonstrates that the individual NA of a DL in a broadband imaging system is one to two orders of magnitude lower than the overall system's NA. This shows that high-NA flat optical elements are not required for high-NA broadband systems. Therefore, nanocomposite-enabled EGs can unlock the full potential of DOEs for broadband optical systems, whereas other technologies cannot fulfill their high efficiency requirements.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Diffractive optical elements; Diffractive optics; Nanocomposites; Optical design; Optical systems; Propagation; Stray light